GPS network for the deformation control in the Mount Melbourne area (Antarctica) : preliminary results of third measurements campaign - O. Al Bayari; F. Radicioni; L. Vittuari; CAPRA, Alessandro (Nautilus, 1996)
GPS network for the deformation control of a volcano located close to italian base in Antarctica.Results analysisi and interpretation.